The Effectiveness of Entrepreneurship Classes in Enhancing Mindfulness as Work Preparedness for Juvenile Theft Offenders at UPT PRSMP Surabaya - Vera Yolanda Gustin; Siti Jaro'ah (International Conference on Psychology and Education (ICPE), 2025)
Juvenile theft offenders often struggle with emotional regulation, low self-awareness, and poor impulse control, hindering their rehabilitation and readiness for reintegration. Conventional interventions, such as legal correction and formal mindfulness programs, have been used to address these issues. However, such methods often lack engagement, particularly among adolescents, and may not align with their developmental needs. This study introduces an entrepreneurship-based mindfulness approach as a more adaptive and engaging alternative. The program integrates creative, hands-on vocational training with implicit mindfulness principles, such as focus, patience, and emotional awareness. This research aims to explore how structured entrepreneurship classes can support mindfulness and work preparedness among juvenile offenders in a correctional facility. Using a descriptive qualitative method, the study involved observations and interviews with 10 participants at UPT PRSMP Surabaya over four weeks of intervention. The findings suggest that participants experienced behavioral improvements such as increased calmness, cooperation, and task focus. These insights demonstrate the potential of entrepreneurship-based mindfulness programs as supportive tools for rehabilitation.